Continuum model validation of gas jet plume injection into a gas–solid bubbling fluidized bed. Issue 9 (31st January 2013) - Rangarajan, Deepak; Curtis, Jennifer S.; Benyahia, Sofiane; Mychkovsky, Alexander G.
<x xml:space="preserve">Abstract</x> A continuum gas–solid model that includes descriptions for solid frictional stress and a turbulent gas phase is evaluated against published experimental measurements of mean and fluctuating velocity inside the jet plume region of a bubbling fluidized bed with a high‐speed vertical jet injection. The main uncertainties in closure relations necessary in the continuum model are first identified and then determined using available experimental data. The overall model shows good agreement with both the gas and particle experimental velocity profiles. The trends in the centerline mean and fluctuating velocity with change in the fluidized state of the emulsion are also captured favorably. Main deviations between the model and experiment are noted and possible reasons for the mismatch are discussed. © 2013 American Institute of Chemical Engineers AIChE J, 59: 3247–3264, 2013